2023
DOI: 10.54112/bbasr.v2023i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Virus and Genotypes in the Region of Khyber Pakhtunkhwa Pakistan

M GOHAR,
IU REHMAN,
J AHMAD
et al.

Abstract: About 3% of Pakistani population is the carrier of hepatitis B virus, and infection is growing at a steady rate. The current study reviews the situation of HBV in the KP population. Approximately 85 studies related to the prevalence of HBV and its genotypes in this region were searched using various databases. The mean and standard deviation based on collected data indicates an HBV prevalence of 110.09%±3.71 in general population, 2.51% ± 0.01 in healthy blood donors, 1.74% ± 0.01 in health care workers, 3.40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Ciprofloxacin, a broad-spectrum fluoroquinolone antibiotic, was selected as the standard drug S* owing to its efficacy against both gram-positive and gram-negative bacteria (Suleman 2016 ; AMIN et al 2023 ; Hassan et al 2023 ). It may act by inhibiting the activity of crucial bacterial enzymes, namely topoisomerase IV and topoisomerase II (DNA gyrase), which play vital roles in the separation of bacterial DNA (Khan et al 2018 ; GOHAR et al 2023 ; Ullah et al 2023a , b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciprofloxacin, a broad-spectrum fluoroquinolone antibiotic, was selected as the standard drug S* owing to its efficacy against both gram-positive and gram-negative bacteria (Suleman 2016 ; AMIN et al 2023 ; Hassan et al 2023 ). It may act by inhibiting the activity of crucial bacterial enzymes, namely topoisomerase IV and topoisomerase II (DNA gyrase), which play vital roles in the separation of bacterial DNA (Khan et al 2018 ; GOHAR et al 2023 ; Ullah et al 2023a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, bacterial, viral, and other microbial infections can all cause respiratory tract infections. Specific bacterial pathogens, including Staphylococcus aureus , Streptococcus pneumonia , and hemophilic influenza , were commonly responsible for bacterial respiratory infections (Wu et al 2021 ; GOHAR et al 2023 ; Hassan et al 2023 ). Hemophilic influenza is not only a primary cause of pneumonia but can also lead to bronchitis and sinusitis (Diaz-Diaz et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research in children aged 6 to 11 revealed notable gains in lung function, but not in BMI or CFQ-R ratings; several unfavorable side-effects forced the trial’s termination. Although the effectiveness of the combination therapy is recognized, its usage is restricted due to concerns about drug interactions and safety [ 62 , 76 , 77 , 78 , 79 ].…”
Section: Monotherapy To Triple Combination Therapy (Eti)mentioning
confidence: 99%
“…This genetic variation leads to substituting valine (Val) with methionine (Met) at codon 66 of the proBDNF protein. The Val66Met SNP has demonstrated effects on the intracellular transportation and activity-dependent release of BDNF demonstrated effects on the intracellular transportation and activity-dependent release of (Egan et al 2003 ; Dempster et al 2005 ; Szeszko et al 2005 ; PERVAIZ et al 2021 ; GOHAR et al 2023 ). The Val66Met SNP has a significant influence on BDNF secretion and function.…”
Section: Introductionmentioning
confidence: 99%